Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(2x+2y\)
\(=2\left(x+y\right)\)
b) \(5x+20y\)
\(=5\left(x+4y\right)\)
c) \(6xy-30y\)
\(=6y\left(x-5\right)\)
d) \(5x\left[x-110-10y\left(x-11\right)\right]\)
\(=5x\left(x-110-10xy+110\right)\)
\(=5x\left(x-10xy\right)\)
\(=5x^2\left(1-10y\right)\)
e) \(x^3-4x^2+x\)
\(=x\left(x^2-4x+1\right)\)
f) \(x\left(x+y\right)-\left(2x+2y\right)\)
\(=x\left(x+y\right)-2\left(x+y\right)\)
\(=\left(x+y\right)\left(x-2\right)\)
h) \(5x\left(x-2y\right)+2\left(2y-x\right)\)
\(=5x\left(x-2y\right)-2\left(x-2y\right)\)
\(=\left(x-2y\right)\left(5x-2\right)\)
i) \(x^2y^3-\dfrac{1}{2}x^4y^8\)
\(=x^2y^3\left(1-\dfrac{1}{2}xy^5\right)\)
j) \(a^2b^4+a^3b-abc\)
\(=ab\left(ab^3+a^2-c\right)\)
Lời giải:
\((x^3+x^2y+xy^2+y^3)(x-y)=[x^2(x+y)+y^2(x+y)](x-y)\)
\(=(x^2+y^2)(x+y)(x-y)\)
\(=(x^2+y^2)(x^2-xy+yx-y^2)=(x^2+y^2)(x^2-y^2)\)
\(=x^4-x^2y^2+y^2x^2-y^4=x^4-y^4\) (đpcm)
1, \(x^2+4x-2xy-4y+y^2=\left(x^2-2xy+y^2\right)+\left(4x-4y\right)=\left(x-y\right)^2+4\left(x-y\right)=\left(x-y\right)\left(x-y+4\right)\)
2, \(x^3-2x^2+x=x\left(x^2-2x+1\right)=x\left(x-1\right)^2\)
3, \(2x^2+4x+2-2y^2=2\left(x^2-y^2\right)+2\left(2x+1\right)=2\left(x^2+2x+1-y^2\right)=2\left[\left(x+1\right)^2-y^2\right]=2\left(x+1-y\right)\left(x+1+y\right)\)
4, \(x^4-2x^2=x^4-2x^2+1-1=\left(x^2-1\right)^2-1=\left(x^2-1-1\right)\left(x^2-1+1\right)=\left(x^2-2\right)x^2\)
5, \(x^3+2x^2y+xy^2-9x=x\left(x^2+2xy+y^2-9\right)=x\left[\left(x+y\right)^2-3^2\right]=x\left(x+y-3\right)\left(x+y+3\right)\)
6, \(x^3-\frac{1}{4}x=x\left(x^2-\frac{1}{4}\right)=x\left(x-\frac{1}{2}\right)\left(x+\frac{1}{2}\right)\)
7, \(2x-2y-x^2+2xy-y^2=\left(2x-2y\right)-\left(x^2-2xy+y^2\right)=2\left(x-y\right)-\left(x-y\right)^2=\left(x-y\right)\left(2-x+y\right)\)
8, \(\left(2x+3\right)^2-\left(x+1\right)^2=\left(2x+3+x+1\right)\left(2x+3-x-1\right)=\left(3x+4\right)\left(x+2\right)\)
PTĐTTNT???
\(x^4+x^2y^2+y^4\)
\(=\text{ }\left[\left(x^2\right)^2+2.x^2.y^2+\left(y^2\right)^2\right]-x^2y^2\)
\(=\left(x^2+y^2\right)^2-\left(xy\right)^2\)
\(=\left(x^2+xy+y^2\right)\left(x^2-xy+y^2\right)\)